(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Informatization and unprecedented advances in technology make it necessary to adapt the development of skills in the information society. At present, information and communication competence becomes an urgent need and a prerequisite for the success of future specialists, so it is necessary to increase the efficiency of work, to communicate, to access information and to receive services. Information and communicative competence of a future expert is a complex formed by the individual qualities that provide flexibility and willingness to change; efficiency of professional work in the conditions of informatization of a modern society in order to acquire information and communicative competence. Despite numerous studies of the problem connected with the formation of information and communication competence, the actual level of knowledge and skills of graduates of Russian schools in this area is quite low. Therefore the problem of the search tools to more effectively develop the information and communication competence of a future specialist is highly relevant. Today information educational environment becomes one of the main means of training meeting the requirements of a competence approach. These features are provided by the didactic specificity of methodological support of educational environment, by shifting the emphasis from educational activity of the teacher to the use of active and interactive teaching methods, active and independent cognitive activity of students; orientation in learning not only to the result of training, but also the process of development of new information and applying it to produce results; giving students the freedom of choice of means of implementation of the training task. Subject information and educational environment can be defined as an open educational system formed on the basis of information of educational resources, computer training facilities, modern means of communication, educational technology which is aimed at the formation of creative, intellectual and social development of the individual. As the theoretical research and practical experience show, the subject e-learning environment in combination with active and interactive teaching methods, individual and group creative tasks in the context of future professional activity of a specialist is one of the leading factors in the formation of its information and communication competence. The author describes in detail the stages of the electronic textbook development, as well as web quests in the teaching of philological sciences at the university, and enumerates a number of advantages of their use.